Greenhouse Gases from Reservoirs Caused by Biochemical Processes : Interim Technical Note - Liden, Rikard (World Bank, Washington, DC, 2014)
A decade ago, the contribution of greenhouse gases (GHGs) from reservoirs was estimated to be up to 7 percent of global GHG emissions from all sources. Much research on GHG emissions from reservoirs has subsequently been conducted and recent studies have indicated corresponding global estimate to be less than 1 percent. However, these studies still have a limited coverage of ecosystems and geographic areas, and, more critically, almost none of them have measured the long-term change in GHG emissions over many years. Therefore, the research conducted to date has shown disparity in GHG emission magnitudes from reservoirs, which has caused a debate on methodologies and reliability of results. The purpose of this note is to provide interim guidance to World Bank staff on how to assess GHGs from reservoirs in preparation for dam infrastructure projects. The note describes the major biochemical processes that cause GHGs from reservoirs, provides the status of current knowledge and research, and puts the issue into a global perspective. Based on the state-of-the-art, it makes recommendation on how to assess GHG emissions and how to make preliminary rough estimates of emissions caused by biochemical processes for planned reservoirs.